Coagulopathy in Acute Promyelocytic Leukemia: Can We Go Beyond Supportive Care? - Hambley, Bryan C.; Tomuleasa, Ciprian; Ghiaur, Gabriel (Frontiers in Medicine, 2021)
Acute promyelocytic leukemia (APL) is characterized by frequent complications due to a distinct coagulopathy. While advances in treatments have improved long-term survival, hemorrhagic and thrombotic complications remain the most common causes of death and morbidity. Improved understanding of the mechanisms of the coagulopathy associated with APL may lead to therapeutic interventions to mitigate the risk of hemorrhage and thrombosis.